Learning English in SMPIT Raudhatul Jannah Cilegon City (an Ethnography Research) - Anis Fuad; Zainal Rafli; Ninuk Lustyantie (Loquen, 2018)
This study aims to investigate culture themes in English learning at Islamic junior high school (SMPIT) Raudhatul Jannah Cilegon in academic years 2017/2018. This research conducts a qualitative approach with an ethnography method. The data were collected through observation, interview, and document analysis. The research analysis used Spradley’s terms; domain, taxonomy, and componential analysis, then discovering cultural themes. The research findings showed that 1) Cultural themes that found in English learning at SMPIT Raudhatul Jannah Cilegon have many cultural aspects including rule, custom, attitude, and value; 2) The four cultural aspects are reflected in English learning activities that apply cooperative learning. The results of this research conclude that cultural aspects which contained in English learning at SMPIT Raudhatul Jannah Cilegon become a complement that can improve the quality of learning.